1994
DOI: 10.1093/carcin/15.9.1911
|View full text |Cite
|
Sign up to set email alerts
|

In vitro formation of DNA adducts with bile acids

Abstract: The in vitro experiment was carried out following 32P-postlabeling analysis to determine the DNA-reactive bile acids present in the human body. The unconjugated and conjugated forms of cholic (CA), chenodeoxycholic (CDCA), deoxycholic (DCA) and lithocholic acid (LCA) were added to calf thymus DNA followed by 1 h of incubation at 37 degrees C. After the incubation the mixture was analyzed by the nuclease P1 modification of 32P-postlabeling. Among the 12 bile acids tested, our results showed that unconjugated CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 0 publications
0
20
0
1
Order By: Relevance
“…Interestingly, bile acids may directly bind to DNA; 32 P-labeling analysis of DNA-reactive bile acids provided evidence of DNA-adduct formation. 42 Conversely, others have shown that bile acids do not bind covalently to DNA. 43 It is also possible that UDCA interacts with transcriptional factors, thereby modulating several genes of the E2F-1/ Mdm-2/p53 apoptotic pathway, as previously demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, bile acids may directly bind to DNA; 32 P-labeling analysis of DNA-reactive bile acids provided evidence of DNA-adduct formation. 42 Conversely, others have shown that bile acids do not bind covalently to DNA. 43 It is also possible that UDCA interacts with transcriptional factors, thereby modulating several genes of the E2F-1/ Mdm-2/p53 apoptotic pathway, as previously demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…LCA is poorly water-soluble and not reabsorbed well by the gut. At higher concentrations, LCA forms DNA adducts and inhibits DNA repair enzymes [117][118][119]. High colonic levels of LCA are implicated as a factor in colorectal cancer [120], and LCA promotes colon cancer in animal models [121].…”
Section: Bile Saltsmentioning
confidence: 99%
“…It does not appear that bile acids are direct mutagens or carcinogens, because no bile acid-DNA adducts have been detected either in the colon and liver of rats that were administered various bile acids by gavage, or in cultured cells exposed to bile acids [11]. Other studies have focused on the ability of secondary bile acids to act as tumor promoters by stimulating signal transduction and cancer-promoting genes.…”
Section: Introductionmentioning
confidence: 99%